(untitled) (Tempo e Argumento, 2013)
History and memory are not two exactly surimposable concepts and they are even less as soon as the past they describe has a traumatic history’s mark. In the heart of the struck relationships Clio and Mnemosyne then have, records are standing. In cases like these, the treatment they receive forms a special look-out post to see the innumerable issues that the recall of the past rises. If there are some who are doubtful of this, French works and essays of which this paper offers to summarize the major points, are good example of the validity of this assertion. As a counterpoint to the covetousness the records arouse, they show the power that our occidental representations attribute to their ownership. Target of another kind of abuse, the roughly handled records feed controversies, and by these ones, alliances change and the split lines move. On the memory scene, activists, professional historians, politicians, lawmakers and judges play a complicated game in that, as from the 80s, the witnesses take a part, just as the historians who came from the ranks of memory communities. To the test of proofs, memories knock together. Dominating and dominated, victimized and heroic, subjective and objective, emotional and rational memories confront each other in a crash of which the jolts inevitably affect history as a discipline.